Exploring BeagleBone Tools and Techniques for Building with Embedded Linux - Molloy, Derek (Wiley, 2014)
guidance and online peer support help you transition from beginner to expert as you master the techniques presented in Exploring BeagleBone, the practical handbook for the popular computing platform
Description based on publisher supplied metadata and other sources
Keywords: BeagleBone (Computer); Embedded computer systems; JavaScript (Computer program language); Linux; BeagleBone